"Quality of life of patients after surgical treatment of cervical spine metastases". Issue 1 (December 2016) - Guzik, Grzegorz
Abstract Background Metastases of malignant neoplasms to the cervical spine are relatively rare. The most common symptom of metastatic disease is pain. Symptoms associated with roots damage or spinal cord compression indicate locally advanced disease. In a large number of patients, surgical treatment brings benefits such as pain reduction and improvement of the quality of life. Pain intensity, neurological status, and quality of patients' lives are measured with the VAS, Frankel, and Karnofsky scales. Methods Symptoms of the disease, morphology of the metastasis and treatment outcomes were evaluated in 57 patients treated surgically because of metastases to the cervical spine over the period 2010–2014 in Brzozów. The morphology of the metastases was assessed on the basis of CT and MR examinations. Pre- and postoperative functional status of the patients was evaluated using Karnofsky scale. The intensity of pain was assessed with VAS and the neurological status was evaluated by using Frankel's grades. Anterior approach was employed in 16 patients, posterior approach in 30 patients, and postero-anterior approach in 11 patients. The inter-group differences were evaluated using the U Mann–Whitney and Wilcoxon Matched Pairs test. All statistical analyses were performed by using Statistica 10. A value ofP < 0.05 was considered statistically significant. Results The majority of patients suffered from pain associated with instability of the spine. Multi-level metastases were noted in 40 patients, while in 17 patients 1 vertebra was involved. In 51 patients the metastases caused pathological fractures of the vertebrae. The most common neurological complications was observed in patients with multi-level tumors and with pedicles involvement. After surgery patients functional status improved and pain intensity decreased. The best results (statistically significant) were observed in patients operated with anterolateral approach. Complications were scarce. Two patients required reoperation due to infection. Conclusions Surgical treatment of metastases to the cervical spine gives good outcomes and it ought to be a treatment of choice. Proper and multifaceted qualification of the patients for different treatments is of vital importance.